2019
DOI: 10.1111/dsji.12185
|View full text |Cite
|
Sign up to set email alerts
|

Using Real‐Life Major League Baseball Data in an Introductory Statistics Course

Abstract: A primary goal of introductory statistics courses is to develop a student's ability to think statistically. To motivate students to this end, the literature suggests that statistics courses use exercises that are relevant and familiar to students. Work in educational psychology highlights the importance of connecting new concepts to pre-existing knowledge, mental models, or schema. One method to meet these criteria is to develop exercises and problems that use real-life data. While real-life data provide a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Such students may view learning research as a “necessary evil” to be tolerated in order to achieve one's academic or career goals or enhance one's ability to “think like a scientist.” However, the takeaway of the qualitative data is that most students do not see the relevance or applicability of research subjects to their degree or intended careers. This finding resonates with prior work suggesting that because quantitative subjects are depicted as research and theory-focused, students consider these to have minimal practical application (Uttl et al, 2013; Vittengl et al, 2004; Wathen & Rhew, 2019). Further, this finding highlights disconnect between educators’ (and accrediting bodies’) opinions and those of students.…”
Section: Discussionsupporting
confidence: 81%
“…Such students may view learning research as a “necessary evil” to be tolerated in order to achieve one's academic or career goals or enhance one's ability to “think like a scientist.” However, the takeaway of the qualitative data is that most students do not see the relevance or applicability of research subjects to their degree or intended careers. This finding resonates with prior work suggesting that because quantitative subjects are depicted as research and theory-focused, students consider these to have minimal practical application (Uttl et al, 2013; Vittengl et al, 2004; Wathen & Rhew, 2019). Further, this finding highlights disconnect between educators’ (and accrediting bodies’) opinions and those of students.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have indicated advantages of situational mathematics (e.g., Donovan & Fyfe, 2019;Rubel & McCloskey, 2021;Parker et al, 2018). For example, Using real-life data in statistics courses will stimulate students' interest (Wathen & Rhew, 2019); at the same time, schools around the world have increased the portion of mathematical curriculums that train students to apply learned knowledge into daily life (e.g., Cai, 2012;NCTM, 2000). Situational mathematics can enhance students' comprehension of mathematical concepts by employing concrete examples (e.g.…”
Section: Educational Implicationsmentioning
confidence: 99%
“…First, we prefer using frequencies or counts of people in relatable examples rather than probabilities. As mentioned above, the average person has a poor grasp of probability, which is improved when using relative frequencies and relatable real‐world examples (Wathen & Rhew, 2019). Medical testing examples are particularly useful since most people intuitively understand the difference between testing positive for a condition and actually having the condition.…”
Section: Motivationmentioning
confidence: 99%